2001
DOI: 10.1016/s0736-0266(00)00017-6
|View full text |Cite
|
Sign up to set email alerts
|

BMP signaling stimulates chondrocyte maturation and the expression of Indian hedgehog

Abstract: Mutant BMP receptors were transfected into cultured embryonic upper sternal chrondrocytes using retroviral vectors to determine if BMP signaling is required for chondrocyte maturation and the expression of a key regulatory molecule, Indian hedgehog (Ihh). Chondrocytes infected with replication competent avian retroviruses (RCAS) viruses carrying constitutive active (CA) BMPR-IA and BMPR-IS had enhanced expression of type X collagen and Ihh mRNA. Addition of PTHrP, a known inhibitor of chondrocyte maturation, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
71
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(83 citation statements)
references
References 37 publications
10
71
0
2
Order By: Relevance
“…Hedgehog signaling seems to interact with BMP signaling in regulation of several systems (Murtaugh et al 1999, Pathi et al 1999, Grimsrud et al 2001, and Cbfa1 expression can be induced by BMPs in C3H10T1/2 fibroblasts (Ducy et al 1997). We also observed that BMP enhances proliferation and alkaline phosphatase activity in chondrocytes.…”
Section: Figuresupporting
confidence: 58%
“…Hedgehog signaling seems to interact with BMP signaling in regulation of several systems (Murtaugh et al 1999, Pathi et al 1999, Grimsrud et al 2001, and Cbfa1 expression can be induced by BMPs in C3H10T1/2 fibroblasts (Ducy et al 1997). We also observed that BMP enhances proliferation and alkaline phosphatase activity in chondrocytes.…”
Section: Figuresupporting
confidence: 58%
“…As noted in the previous section, BMPs can regulate Ihh expression in pre-hypertrophic chondrocytes [Grimsrud et al, 2001]. While the mechanism of BMP regulation of Ihh is not known, evidence in both primary chondrocytes as well as chondrocytic cell lines suggest that both Smad proteins and the transcription factor Runx2 could be involved.…”
Section: Stimulators Of Ihh Expressionmentioning
confidence: 86%
“…Tagariello et al (8) have shown that Ucma expression in the developing limb is Indian hedgehog independent. To investigate a potential regulatory effect on Ucma expression by BMP factors, which have been shown to promote chondrocyte maturation toward the hypertrophic phenotype in vitro and in vivo we treated chondrogenic MC615 cells and primary murine rib chondrocytes with increasing amounts of BMP-2 for 24 h (22). Northern blot analysis revealed a dose-dependent repression of Ucma mRNA expression in response to BMP-2 in both MC615 cells and primary chondrocytes (Fig.…”
Section: Bmp-2 Represses Ucma Transcription In Chondrogenic Cells-mentioning
confidence: 97%